2015
DOI: 10.1108/ijmhsc-08-2014-0030
|View full text |Cite
|
Sign up to set email alerts
|

Examining the disjunctures between policy and care in Canada’s Parent and Grandparent Supervisa

Abstract: Purpose – The purpose of this paper is to examine disjunctures between the ways in which Canada’s Parent and Grandparent Supervisa is framed within policy documents and press releases, and how it is actually experienced by older adults and their adult children from the Global South who engage in intergenerational care exchanges once they reunify. Design/methodology/approach – A case study involving qualitative interviews with a married c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 16 publications
0
12
0
2
Order By: Relevance
“…This situation is more severe for recent aged immigrants who were sponsored by their families as they are ineligible for government assistance during the 20-year sponsorship period (Koehn, 2009). Studies have found that less than half of late-life family class immigrants via the Parent and Grandparent Sponsorship Program receive employment income (Ferrer, 2015) and low average earnings (Government of Canada, 2014), which institutionalise financial barriers to care.…”
Section: Macro-system: Broader Structural Determinantsmentioning
confidence: 99%
“…This situation is more severe for recent aged immigrants who were sponsored by their families as they are ineligible for government assistance during the 20-year sponsorship period (Koehn, 2009). Studies have found that less than half of late-life family class immigrants via the Parent and Grandparent Sponsorship Program receive employment income (Ferrer, 2015) and low average earnings (Government of Canada, 2014), which institutionalise financial barriers to care.…”
Section: Macro-system: Broader Structural Determinantsmentioning
confidence: 99%
“…However, the financial requirements and investment from adult children as sponsors penalize low-income households (Spitzer et al, 2006 ). Ferrer has argued that the streamlined super visa program “categorize older adults as ‘visitors’ who must be surveilled and made ineligible for state benefits because of common perceptions that they consume valuable and scarce resources” ( 2015 , p. 264). Even if parents are granted a visa to Canada, they are expected to buy health insurance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, due to the temporary status, parents/grandparents are ineligible for state-provided services and entitlement, and all medical and other caring responsibilities are on the shoulders of immigrant family and/or their parents/grandparents (Ferrer, 2015).…”
Section: Super Visa Is Not a Successful Alternative For Family Reunificationmentioning
confidence: 99%